2020
DOI: 10.1371/journal.ppat.1008959
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 ORF10 is not essential in vitro or in vivo in humans

Abstract: SARS-CoV-2 genome annotation revealed the presence of 10 open reading frames (ORFs), of which the last one (ORF10) is positioned downstream of the N gene. It is a hypothetical gene, which was speculated to encode a 38 aa protein. This hypothetical protein does not share sequence similarity with any other known protein and cannot be associated with a function. While the role of this ORF10 was proposed, there is growing evidence showing that the ORF10 is not a coding region. Here, we identified SARS-CoV-2 varian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 14 publications
2
66
0
Order By: Relevance
“…In addition, ORF10 has highly antigenic epitopes ( Table 3 and Table 4 ), which are promising subunit vaccine candidates awaiting further validation studies in vivo. The role of ORF10 is still controversial, as there are two different views: one view relies on the lack of evidence on ORF10 expression or function in host cells, suggesting that ORF10 is a non-essential and most likely non-expressed protein [ 53 ], while the second view suggests ORF10 as a potential target for vaccine development [ 54 ], which supports our prediction.…”
Section: Resultssupporting
confidence: 79%
“…In addition, ORF10 has highly antigenic epitopes ( Table 3 and Table 4 ), which are promising subunit vaccine candidates awaiting further validation studies in vivo. The role of ORF10 is still controversial, as there are two different views: one view relies on the lack of evidence on ORF10 expression or function in host cells, suggesting that ORF10 is a non-essential and most likely non-expressed protein [ 53 ], while the second view suggests ORF10 as a potential target for vaccine development [ 54 ], which supports our prediction.…”
Section: Resultssupporting
confidence: 79%
“…4 ), these data suggest that the ORF10 protein may only be fleetingly present during infection, if expressed at all. Third, a strain of SARS-CoV-2 in which ORF10 contains a premature stop codon at residue 29 was isolated, and it can still replicate in vivo and in vitro ( 22 ). While most of ORF10, including the N terminus used to bind ZYG11B, is still retained in this strain, this nonetheless implies that the full open reading frame is not required for infection.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothetical 38aa long protein has been described as ORF10. Perhaps this one is the least attractive of the accessory proteins, since it has been shown that it is not essential in human SARS-CoV-2 infection ( 65 ). Its sequence is not similar to other coronavirus, and specific biological functions have not been described yet.…”
Section: Accessory Proteins Of Sars-cov-2mentioning
confidence: 99%